Four stanniocalcin genes in teleost fish: Structure, phylogenetic analysis, tissue distribution and expression during hypercalcemic challenge - Schein, V; Schein, Vanessa (2014)
Stanniocalcin (STC), first isolated from the corpuscles of Stannius (CS) of teleost fishes and a systemic regulator of mineral metabolism, is present in all vertebrates as two isoforms, STC1 and STC2, encoded by separate genes. Here we show that the genome of Tetraodon nigroviridis, and other teleosts, possess duplicate genes for each STC isoform, designated stc1-a and -b, and stc2-a and -b. Stc1-a was cloned from CS, stc2-a from muscle and the two novel cDNAs, stc1-b and stc2-b, from brain. However, stc2-b was isolated as a conjoined (read-through) transcript with bod1 (bi-orientation defective 1, or FAM44B), and two additional alternative conjoined transcripts were also isolated. The predicted STC products shared the typical vertebrate 10 conserved cysteine residues and N-linked glycosylation motifs, in addition to specific features. Gene structure was generally conserved with four exons and three introns with the exception of stc1-a which gained an extra intron in exon three, originating one extra exon. Gene order and synteny is also maintained across vertebrates and the cpeb4 gene identified in the homologue region of the chordate Ciona was linked to vertebrate stc2 but not stc1. Immunohistochemistry in different species revealed that STC1-A was found only in CS and in a few cells in kidney. STC1-B had a restricted expression and was more prominent in the gills. STC2-A was detected in a variety of tissues, including pituitary, with most abundant immunoreaction in kidney cells and gill rakers and the CS was negative. Expression of stc1-a in CS of Tetraodon was 15-fold (p < 0.05) up-regulated 2 h after transfer from 2.9 mM Ca2+ to 10 mM Ca2+ water and down-regulated after 12 hours to 11-fold lower than 2.9 mM Ca2+ fish (p < 0.05). With the exception of stc1-a in CS, low expression levels and high individual variation were generally found for the expression of stc transcripts in kidney and gills, with no statistically significant changes in response to the hypercalcemic shock. In conclusion, both stc1 and stc2 genes are represented by paralogues in teleosts genomes and the analysis performed suggests that only stc1-a in the CS is involved in extracellular calcium regulation. The widespread distribution of stcs in fish tissues supports pleiotropic roles.